Non-subungual presentation of osteochondroma in toes—A case report with review of literature. (June 2021) - Bansal, Hemant; Veeresh, Vivek; Jarolia, Mansingh; Khare, Ghanshyam Narayan
Highlights: Osteochondroma in toes perpetually have subungual presentation and hitherto non-subungual presentation has not been reported. They are known for surprising, unusual presentations in human skeleton and numerous rare sites of affection have been reported. One must keep osteochondroma in the differential diagnosis of long-standing benign bony swelling at unanticipated locations. Abstract: A 23-year-old male presented with long-standing swelling in the middle of the third toe right side with difficulty in wearing footwear. Clinical examination revealed it as bony hard fixed swelling moving with interphalangeal joint movements. Clinical diagnosis of benign bony swelling was made and radiological investigation demonstrated features suggestive of osteochondroma. En-mass excision of the lesion was done, with histo-pathological confirmation of osteochondroma. Although the subungual presentation of osteochondroma or exostosis in toes is quite common, the astounding non-subungual presentation should also be kept in mind as a plausible differential diagnosis of benign bony swelling in toes.